Anguish, insecurity and fear in the LGBTQIA + population: Deterioration of mental health in the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: to analyze the mental health impairment of the LGBTQIA+ population in the COVID-19 pandemic. Methodology: We performed a systematic review of studies on the Psychosocial Impacts of the COVID-19 pandemic on the mental health of the LGBTQIA+ young adult population. Articles were chosen from the following databases: BVS and PubMed. We use the descriptors LGBT, mental health and COVID-19. The following search filters were applied: articles published in the last 5 years prior to the search date (04.04.2021) and Portuguese and English languages ​​and 20 articles were selected. Results: Due to social isolation and home confinement, several aspects of this group's life were compromised, including: financial, sexual, mental, physical and emotional. As a consequence, the quality of life is impaired and a mixed feeling of anguish, insecurity and fear is aroused, especially for the LGBTQIA+ population, as the individual, a member of this minority group, is not welcomed at home and has ceased contact with their support group due to isolation. Furthermore, while staying at home, LGBTQIA+ children, adolescents and adults are exposed for a prolonged period to unreceptive family members, increasing the rates of physical and emotional aggression, domestic violence, in addition to damage to mental health. Conclusion: Therefore, an analysis of the impacts of the Coronavirus pandemic on the quality of life and on the perpetuation of the social stigma of the group is essential.